Hybrid MHHO-DE Algorithm for Economic Emission Dispatch with Valve-Point Effect - Xia, Aiming; Wu, Xuedong; Bai, Yingjie (Arabian journal for science and engineering (2011), 2021)
Economic emission dispatch with valve-point effect in power systems is a complex multimodal, nonconvex and constrained multi-objective optimization problem. To solve this problem, a hybrid multi-objective algorithm with effective constraint handling method based on Harris hawks optimization and differential evolution is proposed: (1) the concept of Pareto domination is integrated into Harris hawks optimization to deal with economic emission dispatch problem with two conflicting objectives; (2) the optimization mechanism of Harris hawks optimization is modified to enhance its optimization capabilities; (3) a non-dominated sorting method based on new crowding distance, which can obtain Pareto optimal front with excellent uniformity, is used to maintain the external archive and to select the guiders; (4) aiming at the constraints of economic emission dispatch problem, a feasible solution dominated constraint processing method is adopted to obtain feasible solutions; (5) moreover, to enhance the convergence performance of the algorithm, a differential evolution is used to evolve the individuals in the archive. Experimental results on the IEEE 30-bus 6-unit test system demonstrate that the quality of the solutions obtained by the suggested approach is better than that of several existing algorithms.